Elaborately fabricated polytetrafluoroethylene film exhibiting superior high-temperature energy storage performance. (December 2020) - Luo, Suibin; Yu, Junyi; Ansari, Talha Qasim; Yu, Shuhui; Xu, Pengpeng; Cao, Liqiang; Huang, Haitao; Sun, Rong; Wong, Ching-Ping
Highlights: Surface flatness of a polymer significantly affects Eb . PTFE film demonstrates ultrahigh Ud 1.08 J/cm 3 and Pd0.9 0.72 MW/cm 3 at 200°C. A smooth surface is beneficial for achieving self-healing performance. Abstract: Pure polymer film dielectrics with the evident advantage of easy fabrication have been widely used in electronic and electrical systems. But their application is restricted from many high-end fields, such as power electronics and pulsed power devices in which the working temperature is upto 200 °C, where the energy density becomes much lower than that at room temperature. Herein, compact polymer films with a smooth surface are elaborately fabricated through "The King of Plastic" polytetrafluoroethylene (PTFE) nanoparticles by a simple yet effective strategy of heat-treatment. Ultrahigh charge-discharge efficiency (η 94%) and electric breakdown strength (αb 350 kV/mm) are achieved at a high temperature of 200 °C, which result in a high discharged energy density (Ud 1.08 J/cm 3 ) and a high power density (Pd0.9 0.72 MW/cm 3 ). The state of the art performance of the dielectric and energy storage is attributed to the symmetric molecular structure, compact microstructure and smooth surface of the PTFE films. Importantly, the PTFE films coated with Au electrode perform excellent self-healing ability at high temperatures. The elaborately fabricated PTFE film is thus ideal for high-temperature energy storage application and it also can be used as polymer matrix for holding fillers to acquire even higher performance. Graphical abstract: Pure polymer dielectric films with excellent energy storage performance at high temperature are highly desired in electric and electronic industries. The elaborately fabricated PTFE films with controlled microstructure exhibit a high Eb ( 350 kV/mm), high η ( 94%), large Ud ( 1.08 J/cm 3 ), short t0.9 (2.95 μs), high Pd0.9 ( 0.72 MW/cm 3 ) and excellent self-healing ability at 200 °C. Image, graphical abstract